Unexpected Long Survival in Primary Malignant Melanoma of the Male Urethra - Evi Comploj; Salvatore Palermo; Emanuela Trenti; Michele Lodde; Christine Mian; Rodolfo Carella; Armin Pycha (Karger Publishers, 2009)
A case of primary malignant melanoma of the urethra in a 60-year-old male is presented. Despite multiple adverse prognostic factors and against expectations, after a follow-up of 5.5 years he is still alive.